Capacity building for nurses - Sivananthini, Banaya *; David Chinniah, Christina Jayamony *; Ramani, Muniandy * (CodeBlue, 2023)
Capacity building is not merely about acquiring new skills, but it is about strengthening the capabilities of nurses to meet the evolving demands of patient care. By investing in our nurses, we are investing in the future of health care in Malaysia.